2021
DOI: 10.23939/chcht15.03.359
|View full text |Cite
|
Sign up to set email alerts
|

One-Dimensional Hydrogen-Bonded N–H…O in the Hybrid Phosphate: Hirshfeld Surface Analysis and DFT Quantum Chemical Calculations

Abstract: In the present work the 3D-supramolecular network is stabilized by N–H…O and O–H…O hydrogen bonds, by O…N interactions involving the organic cation and inorganic anion as checked by Hirshfeld surface analysis. The van der Waals contacts play a key role in the consolidation of the packing of 4-chloro-2-methylanilinium dihydrogenphosphate[4-CMDHP] structure. In order to support experimental results, density functional theory calculations have been performed using B3LYP functional with 3-21 G basis set. All of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In order to investigate the interaction between C 2 H 5 OH and ferrous oxalate dihydrate crystals in detail, the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) are used to analyze the stability and active sites of quaternary groups [25,32] . The combination of Multiwfn and VMD is employed for the comprehensive analysis of molecular orbitals.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to investigate the interaction between C 2 H 5 OH and ferrous oxalate dihydrate crystals in detail, the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) are used to analyze the stability and active sites of quaternary groups [25,32] . The combination of Multiwfn and VMD is employed for the comprehensive analysis of molecular orbitals.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown that the M06‐2X functional with dispersion correction is a general DFT method for describing nonbonded interactions [22–23] . The geometric optimization and calculation of the complexes were performed at the M06‐2X/6‐311++G(d,p) level to determine the stable configuration of these complexes [24–25] . Natural Bond Orbital (NBO) analysis for the optimized configuration of the complexes was performed at the level of M06‐2X/6‐311++G (d, p) to evaluate the stabilization energy of the complexes [26] .…”
Section: Experiments and Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…The docking score, a vital metric derived from the calculations, holds a pivotal role in the comparative analysis of the activities of the molecules examined in your research [38,39]. It is noteworthy that the molecule exhibiting the most negative numerical value for the docking score is regarded as having the highest activity among the tested compounds [40,41]. This parameter serves as a key tool in evaluating the potential effectiveness of these molecules in their designated roles, such as inhibiting breast cancer proteins [42,43].…”
Section: Resultsmentioning
confidence: 99%
“…N-H-O and O-H-O interactions constituting the largest share of 40%. Mechanical characteristics of organic-inorganic single crystals, such as 4carboxyanilinium dihydrogenphosphate (4CADP), were experimentally investigated using Vickers microhardness, indicating the crystal's belonging to the soft category and providing insight into mechanical strength and porosity [35].In this broader context, the synthesis of organic and inorganic hybrid compounds often involves the combination of organic molecules with inorganic components, yielding materials with distinctive properties. Dihydrogen phosphate compounds, typically containing the H2PO4 − ion, form intriguing hybrids when combined with organic molecules, such as 2-HDETDHP(C5 H14ON + , H2PO4 -).…”
Section: Introductionmentioning
confidence: 99%